Altered Dynamic Functional Connectivity in Early Psychosis Between the Salience Network and Visual Network. (21st May 2022) - Zhao, Lei; Bo, Qijing; Zhang, Zhifang; Chen, Zhenzhu; Wang, Yimeng; Zhang, Douyu; Li, Tian; Yang, Ningbo; Zhou, Yuan; Wang, Chuanyue
Highlights: The disruption of communication between the SN and visual network is an important aspect of the neural basis of psychosis. We confirmed abnormality of dynamic functional interaction between the SN and the DMN in early psychosis. The variability between the ACC and visual regions could distinguish between the FES and the CHR. Abstract: In early psychosis there are alterations in the static functional interaction between the salience network (SN) and higher-order cognitive networks. It is unclear whether these changes extend to the dynamic functional connectivity (dFC) of the SN, and whether the dFC between the SN and low-order networks (e.g., sensory networks) is affected. This study examined the temporal properties of the functional connectivity of the SN in individuals with early psychosis. In this study, selected core regions of the SN included the left and right anterior insula (AIs) and anterior cingulate cortex (ACC), based on independent component analysis of 26 and 20 subjects with first-episode schizophrenia (FES) or at clinical high risk for psychosis (CHR), and 37 healthy controls (HC). The dFC of each region was investigated via sliding window-based analyses with whole brain voxels. We found compared with the HC, in the FES and CHR groups the bilateral AI and ACC showed less variability in dFC with regions in the visual network; the variability between the ACC and visual regions in the FES group was less than that of the CHR; and in the FES and CHR groups the variability in dFC was higher between the right AI and the left precuneus (a core region of the default mode network). This study confirmed abnormality of dynamic functional interaction between the SN and the DMN in psychosis. More importantly, the disruption of communication between the SN and the lower-order brain network is another important aspect of the neural basis of psychosis.